Half a pack of cigarettes a day more than doubles DNA breaks in circulating leukocytes - Mozaffarieh, Maneli (BioMed Central, 2010)
BACKGROUND: The mechanisms by which smoking induces damage is not known for all diseases. One mechanism believed to play a role is oxidative stress. Oxidative stress leads to cellular damage including DNA damage, particularly DNA breaks. We conducted this study to test the hypothesis that smokers have increased DNA breaks in their circulating leukocytes. METHODS: A comparative quantification of single-stranded DNA breaks was performed by comet assay analysis in the circulating leukocytes of ten healthy smokers (average smoking rate: half a pack a day, range: 9-12 cigarettes a day) and ten age and sex matched healthy non-smokers. DNA breaks lead to smaller pieces of DNA, which migrate out of the nucleus forming a tail during gel-electrophoresis. Damage of an individual cell was quantified by the parameters tail moment and olive moment. RESULTS: Smoking had a clear effect on both study parameters (tail and olive moment). Smokers had more than double the amount of ss-DNA breaks in their circulating leukocytes than non-smokers [tail moment: 0·75 AU ([smokers] )compared to 0·2 AU ([non-smokers]); olive moment: 0·85 AU ([smokers] )compared to 0·3 AU ([non-smokers]); both p < 0·001]. CONCLUSION: Smoking half a pack a day interferes with DNA integrity. One potential explanation for the enhanced DNA breaks in smokers is oxidative stress.